Application of UTAUT in analyzing behavioral intention to continue using the online movie platforms - Hao, Yinhua; Yasin, Megat Al Imran; Ng, Boon Sim; Kun, Yu (Anka Publishers, 2022)
This study uses the Unified Theory of Acceptance and Use of Technology (UTAUT) model to explore the influence factors of behavioral intention to continue using the online movie platforms (OMP) with Structural Equation Modeling. In this study, the model was extended to predict customer use of OMP by adding the PV variable into the UTAUT model and the key relationship was established by taking HM as a mediator of all the variables to test the behavioral intention to continue using OMP. Therefore, this study extends the role of HM as a mediator of UTAUT, which incorporates constructs such as PE, EE, SI, FC, and PV, and it has an important influence on customers’ BI to continue using online movie platforms. The results show that PE, SI, and FC (except EE and PV) significantly affect the customers’ HM to continue using the OMP. Moreover, PE and HM (except EE, SI, FC and PV) significantly affect the customers’ BI to continue using the OMP. In addition, HM has a significant mediating effect on PE, SI, and FC for customers’ BI to continue using OMP, while the mediating effect of HM on EE and PV for customers’ BI to continue using OMP is not significant. The results of this study are important for customers and for-profit organizations of OMP to understand the significant factors that influence the use of OMP, which can help them address new issues.